Use of alternative flours in bakery products: a literary review (Research, Society and Development, 2020)
The goal of the present study is to identify and describe scientific articles found in the literature on the use of alternative flours on bakery products, by identifying the most used ingredients in these substitutions. We searched for scientific articles available on databases such as SciELO, Lilacs, SCOPUS, Web of Science, Science Direct and Google Scholar. Using only studies that were published in English and Portuguese. In the search process, terms representative of the research project was used, namely: alternative flours, bread making and bread. 42 articles published between 2003 and 2020 were used. Rice, banana, barley, pea and chia flour provided bakery products with specific nutritional, sensory and physical characteristics, in many cases the sensorial, technological and technical characteristics were enhanced. functional and nutritional, without compromising the final quality of bakery goods and often bringing benefits to consumer health. It is in common agreement between researchers that there is an alternative in the use of these unconventional flours in the bakery industry, because depending on the type of processing, characteristics of the flours and percentage of total or partial replacement, it provides the masses with characteristics that are often superior to products using conventional wheat flour.